Pengaruh Lingkungan Kerja Fisik Dan Pengawasan Terhadap Efektivitas Kerja Pegawai Dinas Pendidikan Kabupaten Kerinci - Pamungkas, Gema Pratama (LPPM Universitas Adiwangsa Jambi, 2019)
In this study there are three variables namely physical work environment variable (X1), supervision variable (x2) and work effectiveness variable (y). The analytical tool used is descriptive analysis, multiple linear regression and coefficient of determination by using the help of statistical software version 20. The sample in this study were 52 people, namely the entire employee of the Kerinci district education office. This research is a descriptive causality study. One type of research is to present a complete picture of social settings or intended to explore clarification about social phenomena or reality by describing a number of variables. Causal research examines the causal relationship of two or more variables. the results of this study indicate that t count = 4.746 while t table with df = (n –k) = 52 - 3 is obtained t table = 2.00856 so that t count> from t table (4.746> 2.00958) or sig <α (0,000 <0,05) so that the physical work environment has a significant effect on work effectiveness. t count <t table (-0,100, <-2,008) or sig <α (0, 920 <0.05). f count> f table (11.440> 3.19) or sig <α (0.00 <0.005) so supervision does not have a significant effect on work effectiveness. the influence of the physical work environment (X1) and supervision (X2) on work effectiveness (Y) is 31.8 while the remaining 68.2% (100% -31.8) is influenced by other variables outside the research.